The Role Of School Principals In Enhancing Job Satisfaction Of Administrative Staff At SMAN 3 Batanghari - Rosa Pina Septiana. S; Mohamad Muspawi; Muhammad Sofwan (Jurnal Niara, 2023)
This research discusses the role of school principals in enchancing job satisfaction of administrative staff at SMAN 3 Batanghari. The aim of this research is to describe the actions taken by principals as well as the obstacles encountered by principals and the methods or solutions used by principals in their efforts to enhance job satisfaction of the administrative staff of SMAN 3 Batanghari school. The research method used is qualitative, involving the school principal, and head of administrative ffairs as respondents. Data were collected through interviews, observations, and documentation. The results of the research indicate that the at SMAN 3 Batanghari is quite positive, looking by job, salary, colleagues, superiors, advancement and working environment in SMAN 3 Batanghari, The obstacles by school principals in increasing the job satisfaction of school administrative staff are the lack of qualified civil servant staff The solution by school principals improving the job satisfaction of the administrative staff of SMAN 3 Batanghari is empower the community and the grad education with professional qualifications in the field of management. The school controls the management and using of available resources in the school, and enhances training to improve the skills of administrative staff